Drum-Buffer-Rope in an engineering-to-order productive system: a case study in a Brazilian aerospace company - Telles, Eduardo Santos; Lacerda, Daniel Pacheco; Morandi, Maria Isabel Wolf; Ellwanger, Rodrigo; Souza, Fernando Bernardi de [UNESP]; Piran, Fabio Sartori (Emerald, 2022)
Purpose: Drum-Buffer-Rope (DBR) is a method to adjust production flows, synchronize the release of materials and enable a process of focused improvement in production systems. Literature on DBR applications in engineer-to-order (ETO) production systems, where customers participate in product design decisions and, consequently, in the way production is planned and executed, is rare. However, the interest in improving production management in ETO systems has received attention from the scientific and business communities. The goal of this research was to evaluate the implementation of DBR in an ETO productive system, critically analyzing the necessary adaptations for its use. Design/methodology/approach: This research was conducted through a case study in a company that manufactures electronic equipment, known as avionics, in the aerospace sector. Findings: In this context, the contribution of this study consists of evaluation of the implementation of DBR in an ETO productive system, describing the implementation and the necessary adaptations of the DBR to the ETO productive system explored, comparing it with the DBR theoretical proposals and Simplified Drum-Buffer-Rope (S-DBR) methods. Originality/value: The study contributes to knowledge by expanding the field of the DBR application to make it more precise, and by applying the theory of constraints, in a general manner, to this type of productive environment.
Keywords: Business operational concepts; Custom engineering; Drum-Buffer-Rope (DBR); Simplified Drum-Buffer-Rope (S-DBR); Theory of Constraints (TOC)